A Molecular Based Approach to Characterize Untypable HCV Genotype - Zahid, Sadia (International Journal of Pathology, 2021)
Background: Hepatitis C virus has the highest morbidity and mortality ratios worldwide infecting around 10 million people/individuals in Pakistan. Due to very high mutation rate, HCV genome is highly diversiﬁed and it is evident from different studies that severity of disease, clinical profile and interferon therapy response depends on HCV genotype. In Pakistan, routine diagnostic tests of HCV genotyping by established protocols (Ohno et al. method) are performed in which untypable or mixed genotypes are not detected.Aims and objectives: The aim of present study is to clone and characterize mutations prevailing in specific fragment of diagnostically detected untypable HCV core; part of the genome involved in genotyping. The current study is based on speculation that a significant HCV variant might be circulating in the population that is not detectable by current genotyping method.Methodology: In our study we characterized untypable HCV samples by cloning, sequencing and in silico study. Phylogenetic analysis was done to estimate evolutionary relationship of untypable samples with other HCV genotypes and quasispecies.Conclusion: This study suggests that new more accurate and advanced genotyping methods using genotype specific primers should be design to resolve the untypable HCV anomaly.